Yield performance of different potato varieties as influenced by Vermicompost (Bangladesh Journal of Botany, 2020)
Use of vermicompost had significant effect on most of the yield contributing parameters studied under the experiment. Results demonstrated that the yield of different potato varieties varied with different combinations of vermicompost. Among the 16-treatment combination, BARI TPS-1 with vermicompost @ 6 t/ha produced the maximum yield (34.75 t/ha); Lady Rosetta with vermicompost @ 6 t/ha produced the maximum yield (35.96 t/ha); Asterix with vermicompost @ 4 t/ha produced the maximum yield (36.01 t/ha) and Courage with vermicompost @ 2 t/ha produced the maximum yield (32.28 t/ha). It may be suggested that the potato growers of Bangladesh may apply vermicompost on their field for maintaining better yield.Bangladesh J. Bot. 49(2): 265-271, 2020 (June)